Besættelsens kulturliv. Beskyttelsesrum, væksthus, modstandslomme og askebægerindustri - Hertel, Hans (Passage - Tidsskrift for litteratur og kritik, 2011)
Hans Hertel: “Danish Cultural Life During the Occupation: Shelter, Greenhouse, Pocket of Resistance, Ashtray Industry” Due to the special Danish occupation conditions, compared to other nations under Nazi rule, in spite of censorship, restrictions and persecution, the arts and media were able to pursue a relatively free course, benefiting from the isolation and the demand for cultural goods. The article analyzes how German propaganda and domestic cultural collaborationism were countered by three currents: an early patriotic revival, a more conscious ‘immune defence’ and an open cultural mobilization and resistance, mostly via illegal media. Furthermore how, in the words of the French critic Tzvetan Todorov, ‘context became text’, i.e. how the reception of classical arts as well as of ‘American’ jazz and youth culture was influenced by the political situation 1940-1945.